Colonic gas homeostasis: Mechanisms of adaptation following HOST‐G904 galactooligosaccharide use in humans. Issue 9 (18th April 2017) - Mego, M.; Accarino, A.; Tzortzis, G.; Vulevic, J.; Gibson, G.; Guarner, F.; Azpiroz, F.
Abstract: Background: We have shown that a galactooligosaccharide prebiotic administration (HOST‐G904) initially increased intestinal gas production and this increase declined back to baseline after 2 week administration. Our aim was to determine the mechanism of microbiota adaptation; i.e., to determine whether the net reduction is due to decreased overall production or increased gas consumption. Methods: In 10 healthy subjects, intestinal gas production and intraluminal disposal was measured before, at the beginning and after 2 week of HOST‐G904 prebiotic administration. Anal gas was collected for 4 hour after a probe meal. Paired studies were performed without and with high‐rate infusion of exogenous gas (24 mL/min) into the jejunum to wash‐out the endogenous gas produced by bacterial fermentation. The exogenous gas infused was labeled (5% SF6 ) to calculate the proportion of endogenous gas evacuated. Key Results: The volume of intestinal gas produced i.e., endogenous gas washed‐out, increased by 37% at the beginning of HOST‐G904 administration ( P =.049 vs preadministration) and decreased down to preadministration level after 2 week administration ( P =.030 vs early administration). The proportion of gas eliminated from the lumen before reaching the anus tended to increase after 2‐week administration (87±3% vs 78±5% preadministration; P =.098). Conclusions & Inferences: Adaptation to regular consumption of HOST‐G904 prebiotic involves a shift in microbiota metabolism toward low‐gas producing pathways, with a non‐significant increase in gas‐consuming activity. Hence, regular consumption of HOST‐G904 regulates intestinal gas metabolism: less gas is produced and a somewhat larger proportion of it is consumed. Abstract : Effect of HOST‐G904 administration on the volume of gas evacuated. Anal evacuation of endogenous gas (produced by bacterial fermentation) 2‐4 hours after a probe meal with and without gaseous wash‐out measured before, at the beginning and after 2 week administration (n=10). With gaseous wash‐out, most endogenous gas produced by colonic fermentation was flushed out and evacuated per anus: gas production increased in the early administration phase and returned back to baseline. Without wash‐out, a large proportion of the gas produced by bacterial fermentation was eliminated from the lumen before reaching the anus and the proportion tended to increase during HOST‐G904 administration. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility-september-2017/id1257018975 Youtube:https://youtu.be/YDdDPaSnzuc